Os Kulina-Pano do Vale do Javari: histórias, memórias e atuação política - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This dissertation is the result of an interdisciplinary study that focused the Kulina-Pano's own narratives on their historical processes and how these processes influenced their interethnic relations. The Kulina-Pano are a northern branch Panoan language-speaking people that lives in the Javari Valley in the southwest of the state of Amazonas. Today the unit known as Kulina-Pano is the result of the merge of two groups of the Mawi’s longhouse living in the São Salvador river and the Kapishtana people that occupied the Pedro Lopes river. These two groups had a relationship marked by conflicts and ended up coming together as a survival strategy of the group after the official contact with the Funai. The Kulina-Pano went through three violent processes that ended up weakening the group: the demographic loss, the conflict with the Matses people that practically decimated the group and caused dispersal among the survivors towards the Curuça's riverbanks and the towns of Benjamin Constant, Tabatinga and Atalaia do Norte. Since them, once the relationship of the Kulina-Pano with non- indigenous peoples and the Funai established, the alliances with non-indigenous peoples became much stronger. Despite all this historical process, the Kulina-Pano managed to regroup and founded their own villages. Currently, the Kulina-Pano are re-establishing close relationships and partnerships with the institutions that operate in the Javari Valley, as a way to have their demands fulfilled. In addition they seek political insertion and recognition in institucional spaces. In order to obtain the data used in this dissertation we proceed with bibliographical research and extensive fieldwork research based on ethnography
Keywords: Povos Pano; Movimento Indígena; Identidade Indígena; Panoan peoples; indigenous movement; CIÊNCIAS HUMANAS